Myristica fragrans Shells as Potential Low Cost Bio-Adsorbent for the Efficient Removal of Rose Bengal from Aqueous Solution: Characteristic and Kinetic Study - Azal Shakir Waheeb; Hassan Abbas Habeeb Alshamsi; Mohammed Kassim Al-Hussainawy; Haider Radhi Saud (Universitas Gadjah Mada, 2020)
In the present study, the Myristica fragrans shells (MFS) was used as low-cost bio adsorbent for the removal of Rose Bengal (RB) dye from aqueous solutions. The characteristics of MFS powder were studied before and after adsorption using different techniques such as Fourier transform Infrared spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA), BET and BJH surface area analysis, Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). Batch adsorption was adopted to evaluate the effect of various parameters on the removal of RB such as; time of contact (5–75 min), initial dye concentration (10–50 mg L–1), adsorbent dose (0.1–1.7 g L–1) and pH (3–12). The results revealed that the coverage of MFS surface by RB molecules involved the formation of ester bond (esterification), and the pore diameter decreased from 190.55 to 2.43 nm when adsorption of RB onto MFS surface occurred. Experimental adsorption data were modelled using isotherm models including Langmuir, Freundlich, and Temkin. Temkin isotherm demonstrated to be the best isothermal model, and the results indicate that the adsorption of Rose Bengal on MFS surface follows pseudo second-order kinetics model. The adsorption of dye at different pH media showed that the esterification process was more preferred in acidic solution.